Efektivitas Pelatihan Empati dalam Mengurangi Konflik Perkawinan pada Pasangan Suami Istri yang Berada pada Tahun Awal Pernikahan - Fatmawati Fatmawati; Rahima Nurviani; Ridha Ilham (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2018)
A conflict in marriage is something that cannot be avoided but must be faced. For this reason, in an effort to reduce or resolve a conflict that occurs, a couple of husband and wife must have effective communication. It includes showing of empathy, which requires the ability of husband and wife to listen to their partners attentively and be willing to receive messages from each other. This study aimed to examine the effectiveness of empathy training to reduce conflict in married couples in their early years of marriage. Empathy training was developed based on 4 empathy techniques, namely self-empathy, accepting others, accurate listening, and perspective taking. Empathy training was conducted on 14 couples who lived in Banda Aceh and Aceh Besar. They were selected using purposive sampling technique. The study used between group/pretest-posttest control group design and the data were collected with marital conflict scale. The results of data analysis showed that empathy training was effective to reduce marital conflict in married couples in the early years of marriage